2013
DOI: 10.1371/journal.pone.0072238
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Doxorubicin/Pluronic SP1049C on Tumorigenicity, Aggressiveness, DNA Methylation and Stem Cell Markers in Murine Leukemia

Abstract: PurposePluronic block copolymers are potent sensitizers of multidrug resistant cancers. SP1049C, a Pluronic-based micellar formulation of doxorubicin (Dox) has completed Phase II clinical trial and demonstrated safety and efficacy in patients with advanced adenocarcinoma of the esophagus and gastroesophageal junction. This study elucidates the ability of SP1049C to deplete cancer stem cells (CSC) and decrease tumorigenicity of cancer cells in vivo.Experimental DesignP388 murine leukemia ascitic tumor was grown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 63 publications
2
48
0
1
Order By: Relevance
“…Several preclinical studies have demonstrated improved antitumor efficacy as compared to doxorubicin in mouse models of myeloma and leukemia. 281283 The drug was found to be well tolerated in a dose-finding phase I study. 284 In this study, 26 patients with tumors refractory to other therapy were treated with escalating doses of SP1049C (5–90 mg/m 2 ).…”
Section: Polymeric Micelles and Nanoparticlesmentioning
confidence: 99%
“…Several preclinical studies have demonstrated improved antitumor efficacy as compared to doxorubicin in mouse models of myeloma and leukemia. 281283 The drug was found to be well tolerated in a dose-finding phase I study. 284 In this study, 26 patients with tumors refractory to other therapy were treated with escalating doses of SP1049C (5–90 mg/m 2 ).…”
Section: Polymeric Micelles and Nanoparticlesmentioning
confidence: 99%
“…In a phase 2 clinical study in patients with advanced adenocarcinoma of the esophagus and gastroesophageal junction, SP1049C demonstrated appreciable anti-tumor activity as a single agent and an acceptable safety profile (59). SP1049C is currently pursued as an agent targeting cancer stem cells, which are highly tumorigenic and intrinsically drug resistant (55,61).…”
Section: Pluronicsmentioning
confidence: 99%
“…We have shown recently that treatment of the mice bearing the leukemia ascitic cells with SP1049C reduces the tumor aggressiveness, in vivo tumor formation frequency and in vitro clonogenic potential of the leukemia cells derived from the treated animals [252]. SP1049C also prevented the overexpression of BCRP and activation of Wnt/β-catenin signaling observed with doxorubicin alone, significantly altered the DNA methylation profiles of the cells and decreased CD133+ cells populations, which displayed CSCs-like properties and were more tumorigenic compared to CD133− cells [252].…”
Section: Nanomedicine-based Therapies Against Cscsmentioning
confidence: 99%
“…SP1049C also prevented the overexpression of BCRP and activation of Wnt/β-catenin signaling observed with doxorubicin alone, significantly altered the DNA methylation profiles of the cells and decreased CD133+ cells populations, which displayed CSCs-like properties and were more tumorigenic compared to CD133− cells [252]. Moreover in the same in vivo leukemia ascitic cells model, the treatment of animals with Pluronic P85 and doxorubicin prevented the development of MDR observed upon long-term treatment of the animals with doxorubicin alone [253].…”
Section: Nanomedicine-based Therapies Against Cscsmentioning
confidence: 99%